Blackwater Event: Water Management and Remediation at a Major Medical Center. (October 2020) - Sampathkumar, Priya; Apenhorst, Debra; Kubly, Al; Keller, Mark; Wright, Alan
Abstract : Background: The CMS and the CDC recommend that all healthcare facilities have an effective water management program (WMP). Our WMP has been in place since 2010; it includes members from facilities operations, infection prevention and control, environmental services, and industrial hygiene. The team meets regularly to discuss current water issues, reviews validation data and water testing reports. Description of event: In April 2018, we suddenly experienced discolored water and sediment at multiple water fixtures throughout the 3.3 million square-foot hospital campus. The hospital incident command structure (HICS) was activated to assist in investigating and managing the situation. Immediate response: Water was deemed unsafe while the cause was being investigated. Bottled water was distributed to 950 hospital patients, and >8, 000 staff and visitors. The impact included alternative methods for hand hygiene, the use of bottled water for food preparation and drinking, and the elimination of showers for patients and staff. The dialysis unit used an independent water supply that was not affected. Investigation and remediation: The hospital had 2 sources of domestic cold water: municipal water and a private well that had been in use since 1912. An investigation revealed that the well pump had malfunctioned, drawing gravel into the potable water supply. This overwhelmed the plumbing, blocked toilets and likely dislodged biofilm from the pipes. Early testing showed high levels of corrosion byproducts (ie, iron, copper, and lead) and bacterial contamination in the water, including presence of Legionella . Remediation involved isolating the well, switching to municipal water as the sole source of potable water, flushing the system, and retesting. Overall, 105 technicians flushed the water system including 6, 000 water fixtures, 125 drinking fountains, and 95 emergency showers and eyewashes; they sanitized and cleaned 130 ice machines and tested 240 backflow preventers. We retested 437 water samples after remediation; all parameters had returned to the normal range. The existing water process flow diagrams were used to guide sampling for water testing. Conclusions: The hospital's water system was brought back on line in 78 hours after the first report of "black water." An active, mature WMP with multiple facilities technicians trained in water sampling enabled a quick response. Coordination through the HICS structure streamlined the response and enabled clear communication throughout the process. Funding: None Disclosures: None